Underwriting and Investment Portfolio Optimization for Insurance Company based on Markowitz Portfolio Selection (Study on BRINS General Insurance) - Hartanto, Randy Adianto Widyo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2021)
This study aimed to compare the performance of insurance portfolios based on Modern Portfolio Theory (MPT) and actual actively managed insurance portfolios. This study also compared the performance of a predictive insurance portfolio based on MPT and actual actively managed portfolio. A sample of the 32-month report of underwriting and investment performance in BRINS General Insurance was analysed using descriptive statistics, and Wilcoxon signed-rank test. This study found no significant difference between the performance of a portfolio based on MPT and the performance of the actual actively managed portfolio. However, the MPT based portfolio significantly underperformed compared to the actual actively managed portfolio when used predictively.Keywords: Modern Portfolio Theory, Insurance Portfolio, Underwriting Portfolio, Investment Portfolio.